Case report: Development of clonal hematologic disorders from inherited bone marrow failure - Cermak, Jaroslav (Frontiers in Oncology, 2024)
Inherited bone marrow failure (IBMF) syndromes are caused by mutations forming pathologic germline variants resulting in the production of defective hematopoietic stem cells (HSC) and in congenital failure in the production of one or more blood lineages. An acquisition of subsequent somatic mutations is determining further course of the disease. Nevertheless, a certain number of patients with IBMF may escape correct diagnosis in childhood, especially those with mild cytopenia and minimal clinical features without non-hematologic symptoms.These patients usually present in the third decade of life with unexplained cytopenia or myelodysplastic syndrome (MDS). We report 2 patients with IBMF who were correctly diagnosed between 20 and 40 years of age when they were referred with progressive MDS with adverse prognostic factors that affected their outcome. IBMF syndromes should be excluded in all patients below 40 years of age with unexplained cytopenia. Early hematopoietic stem cell transplantation (HSCT) is the treatment of choice in these patients.